ANALISIS PENYAJIAN INFORMASI KINERJA DALAM RANGKA IMPLEMENTASI SAKIP PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN DI PROVINSI SULAWESI UTARA - Tampemawa, Patrycia; Saerang, David P.E.; Tangkuman, Steven (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The presentation of performance information is a part of the implementation of SAKIP in government institutions where the presentation of performance information presented in accordance with applicable regulations can be utilized to make dicisions and steps that must be taken in the future in improving institute performance. This study aims to determine and analyze the presentation of performance information in the context of SAKIP implementation at the North Sulawesi Province Educational Quality Assurance Institute that has been presented in accordance with regulations. The analysis method used descriptive qualitative. The result of this study indicate that the presentation of performance information in the institutions studied has not been presented in accordance with regulations because in 14 performance indicators, not all indicators are equipped with information that must be presented as in the regulations.